(untitled) (Current Horticulture, 2024)
The experiment was conducted with three levels each of storage temperature (2.1-2.50c, 6.5-7.50c and 8.0-10°c) and preservation media (sawdust, cocodust and combination of both in equal quantities) from June 2019 to May 2020 at Floriculture Division, Horticulture Research Centre, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh, to find out the optimum storage temperature and suitable media for Lilium (Lilium spp.) bulb preservation and also to see their effect on flower and bulb production in the next flowering season. The bulbs under cool temperature (2.1-2.50c) with sawdust produced minimum sprout (22.0%), shorter root (3.25cm) and shoot (0.55cm) and gained the minimum weight 30, 60, 90 and 120 days after storage (1.42, 2.35, 3.07 and 3.20%, respectively) which ultimately protected bulbs from deterioration during storage period. The two other temperature (6.5-7.50c and 8.0-10.00c) including all media produced 100% sprouting and poor performances in other parameters. Though non-significant variations were recorded in flower, bulb and bulblet production from bulb kept in storage in relation to combination of temperature and media but bulbs preserved in various media at cool temperature (2.10c-2.50c) showed better performances on growth, flowering, bulb and bulblet production in next flowering season.